2007
DOI: 10.1007/s10562-006-9000-x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted catalysis for the destruction of CFC-12 in atmospheric pressure gas streams using TiO2

Abstract: A non-thermal, atmospheric pressure plasma with a titanium dioxide catalyst were combined to destroy difluorochloromethane, CCl 2 F 2 , (CFC-12) in gas streams of nitrogen and air using two configurations; one where the catalyst was incorporated directly into the plasma and the other where the catalyst was downstream of the plasma. The single stage reactor, in both gas streams, gave significant enhancement of the CFC-12 destruction with high energy efficiency. Both configurations decreased NOx production when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 32 publications
4
47
0
Order By: Relevance
“…However, UV radiation generated by plasma discharges is not always the controlling factor to activate photocatalysts 40 . Whitehead has suggested that electron-hole pairs can be created by electron impact upon the surface of photocatalysts since DBD can generate electrons of very similar energy (3 -4 eV) to the photons 13,41 , as shown in Eqs. 14-15.…”
Section: Methodsmentioning
confidence: 99%
“…However, UV radiation generated by plasma discharges is not always the controlling factor to activate photocatalysts 40 . Whitehead has suggested that electron-hole pairs can be created by electron impact upon the surface of photocatalysts since DBD can generate electrons of very similar energy (3 -4 eV) to the photons 13,41 , as shown in Eqs. 14-15.…”
Section: Methodsmentioning
confidence: 99%
“…For both IPC as PPC configuration, heterogeneous catalyst material can be introduced into the reactor in several ways ( Fig. 1c) [24] demonstrated that a variety of catalysts which were originally investigated in the field of thermal catalysis show similar synergy when combined with NTP. These kind of catalysts include platinum-based catalysts [25], protonic zeolites, modified Y-zeolites, de-aluminated Y-zeolites, NaX and NaY zeolites, HZSM-5-supported manganese oxides and LaCoO 3 .…”
Section: Plasma Catalytic Mechanismsmentioning
confidence: 99%
“…Short-living oxidizing species cannot reach this post plasma catalyst [2]. It is clear that mainly ozone is decomposed catalytically, forming molecular and highly active atomic oxygen [21,24,44]. This phenomenon is described for a number of catalysts such as silica gel, porous alumina and metal oxides [8,11].…”
Section: Physical-chemical Effects During Plasma Catalytic Processesmentioning
confidence: 99%
“…Degradation of the CFC-12 occurs through both reductive and oxidative processes on the TiO 2 [11]. In the plasma-catalysis system, it is thought [12] that the electrons in the discharge which typically have a mean energy of ~3.5 eV create electron hole-pair states in an analogous manner to UV excitation TiO 2 + e -(>3.2 eV) → h + + eIn this case, the plasma discharge is changing the electrical properties of the catalyst. Inspection of Fig.…”
Section: Destruction Of Cfc-12 Using Plasma Catalysismentioning
confidence: 99%